(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
The present work was conducted to study the sub-acute toxicopathological changes of relief in mature male rats . Thirty male rats aged (10) weeks and weighted (60 -120) gm were divided equally into (2) groups as follows: Group I: Rats served as control group and received distilled water for 30 days . Group II: Rats served as experimental group and received (by gavage 500 mg /kg b.w ) one tablets of relief (composed of Diclofence sodium 50mg , paracetamol 500 mg ,chlorpheniramine malete 4 mg and magnesium trisilicate 100 mg ) diluted in 10 ml of distilled water . Specimens from, liver, kidneys, testes, epididymis ,brain and spleen, were dissected out for histopathological examination. Results showed severe histopathological changes in all selected tissues as a results of sub acute toxicity of relief tablets.